Identification and comparison of oil compounds derived from pyrolysis of sound wood and decayed wood of beech by using Gas Chromatography and Mass Spectrometry (GC/MS) - Saeed Hasani (Regional Information Center for Science and Technology (RICeST), 2015)
AbstractAmong the forest diseases, fungi are the most important factors that cause irreparable losses to the wood in standing trees and logs. Fungi are the cause of contamination and decay of trees and timbers in forest or in the stock of factories. Decayed woods are one of the biomass resources and a great amount of decayed woods in the forests are not viable. In this study some experiments were conducted in order to investigate the effect of Coriolus versicolor decay on compounds obtained from beech wood (Fagus orientalis L.) pyrolysis and preparation of various and valuable chemicals. Separation and identification of chemical compounds in sound wood and decayed wood of beech was conducted by using pyrolysis method at 500° C and in nitrogen atmosphere. Separation and identification of extracted chemical compounds was carried out using sailylation of these compounds by N, O-bis (trimethylsilyl) trifluoroacetamide and also using Gas Chromatography and Mass Spectrometry method. Totally, 23 compounds were identified in sound beech wood which most of these compounds, in this temperature, are related to 2,6-dimethoxyphenol and 3-hidroxy-4-methoxy benzoic acid; and 31 compounds were detected in decayed beech wood that most of them are related to Cyclononasiloxane octadecamethy and 4-(3,4-Dimethoxybenzylidene)-1-(4-nitrophenyl) and also 17 compounds were detected the same in sound and decayed wood.